JÜDISCH-CHRISTLICHE BEGRÜNDUNG DER MENSCHENWÜRDE UND AKTUELLE GESELLSCHAFTLICHE HERAUSFORDERUNGEN (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Judeo-Christian Foundation of Human Dignity and Current Social ChallengesHuman dignity is currently increasingly in the focus of social debates and is becoming more and more important for the survival of a pluralistic social structure. Despite secular normative justification of human dignity, which today is fundamental to the democratic order, this article outlines the biblical-theological justification of human dignity. Starting from the divine image impressed on man, a tense relationship in the biblical human beings becomes clear. Despite denominational differences, there is a common denominator that coincides with secular understanding. The reflection and respect for human dignity are especially important in the context of modern research, economic and technological progress and for the freedom of religion.